Efforts to Increase Interest in Reading Using Digital Comics as a Learning media Indonesia Language Subject SDN 19 Rantau Selatan Labuhan Batu Regency - Maradona Harahap; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to determine the effect of using digital comic media on reading interest of fourth grade students of SDN 19 Rantau Selatan. The background of this study is the low interest in reading of students caused by the lack of interesting learning media. The research method used is a quantitative method with a quasi-experimental research design. The research sample consisted of two classes, namely the experimental class (IV-A) consisting of 26 students who used digital comics in learning and the control class (IV-B) consisting of 27 students who used conventional methods. The research instrument was a questionnaire that measured students' reading interest before and after treatment. The results of the study showed a significant increase in reading interest in the experimental class after the use of digital comics. The average reading interest score in the experimental class increased from 34.96 to 43.73, while in the control class the increase was not significant with an average of 34.44. The results of the t-test showed that the use of digital comics had a significant positive effect on increasing students' reading interest with a tcount = 5.548, which was greater than ttable = 1.675 at a significance level of 5%. Thus, this study concludes that digital comics are an effective learning medium in increasing elementary school students' reading interest. This study provides recommendations for teachers to utilize digital comics as an alternative in learning Indonesian to increase students' reading interest